ANALISIS PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS KOMINFO KABUPATEN WONOGIRI - Rahayu Kinasih; Priscilia Uning; Ahmad Husin; Elida Zia'ul Huda (STIE Wijaya Mulya, 2024)
The formulation of the problem in this research is: Does training influence job satisfaction for Wonogiri Regency Communication and Information Service employees? Does motivation influence job satisfaction for Wonogiri Regency Communication and Information Service employees? Wonogiri Regency Communication and Information Service Employees?, Does Motivation influence the Performance of Wonogiri Regency Communication and Information Service Employees?, Does Training influence the Performance of Wonogiri Regency Communication and Information Service Employees through job satisfaction?, Does Motivation influence the Performance of Wonogiri Regency Communication and Information Service Employees through job satisfaction?. The research results showed that the effect of training on job satisfaction was obtained with a t-count value of 1.897 > t-table 1.678 with a significance level (ï²) of 0.058 (significant). There is an influence of motivation on job satisfaction because the t-value obtained is 4.579 with a significance level (ï²) of 0.000 (significant). Because the t-count value is 4.579 > t-table 1.897, there is an influence of motivation on the work motivation of Communication and Information Service employees. There is an influence of Job Satisfaction on Performance because the t-value obtained is 4.396 with a significance level (ï²) of 0.000 (significant). Because the t-count value is 4.396 > t-table 1.897, there is an influence of Brand Image on Purchase Intention. There is no influence of training on performance because the t-value obtained is 1.250 with a significance level (ï²) of 0.212 (not significant). Because the t-count value is 1.250 < t-table 1.897, there is an influence of motivation on the performance of the Wonogiri Regency Communication and Information Service. There is an influence of motivation on performance because the t-value obtained is 3.811 with a significance level (ï²) of 0.000 (significant). Because the t-count value is 3.811 > t-table 1.897, there is an influence of motivation on the performance of the Wonogiri Regency Communications and Information Service. There is no influence of discipline on performance through job satisfaction because the t-value obtained is 1.816 with a significance level (ï²) of 0.070 (not significant). Because the t-count value is 1.816 < t-table 1.897, there is no influence of training on the performance of the Wonogiri Regency Communications and Information Service through job satisfaction. There is an influence of motivation through job satisfaction because the t-value obtained is 2.986 with a significance level (ï²) of 0.003 (significant). Because the t-count value is 2.986 > t-table 1.897, there is an influence of motivation on the performance of the Wonogiri Regency Communication and Information Service through Job Satisfaction.Â Keywords: Training, Motivation, Performance